The Importance Of Human Resources (Hr) Management In Company - Lia Marthalia (Journal of World Science, 2022)
Introduction: Human resources have an essential role in realizing development. Human quality is a top priority in a company. So the need for human resource management in managing human resources in the company. Thus, this study aims to understand the importance of human resource management in a company. Methods: The method used is library research based on a qualitative approach. This literature study is to obtain data researchers collect, analyze, and organize, sources derived from articles, books, reports, and other research on human resource management. Results: The results obtained in this study are the importance of human resource management because it benefits the company, including 1) companies can utilize existing human resources competently, 2) productivity of existing employees is increasing, and 3) determination of employee needs/ labor. 4) handling of employment information, and 5) research. Conclusion: Human resource management is essential because it benefits the company, including the company can utilize existing human resources well, the productivity of existing employees is increasing, determining the needs of employees/labor—handling of employment information, and research.